Efficiency of Dried Cassia fistula L. Pod Extracts against Dengue Vector, Aedes aegypti L. (Diptera: Culicidae) via Larvicidal, Pupicidal and Adulticidal Potentials (Early view) - Prachumporn Lauprasert, Komsorn Lauprasert; Kongkaew Yaoup (Tropical Life Sciences Research, 2026)
The growing resistance of Aedes mosquitoes to synthetic insecticides and the environmental hazards associated with traditional management approaches underscore the pressing necessity for biodegradable alternatives. This research assessed the bioefficacy of Cassia fistula pod extracts (seed, fruit pulp, and fruit peel) against Aedes aegypti at various developmental stages (larvae, pupae, and adults) and revealed significant anthraquinone chemicals. Powdered pod materials were extracted using 70% methanol and ethyl acetate using Soxhlet extraction, and their chemical components were analyzed using LC-MS. Bioassays were performed on both laboratory and field strains of A. aegypti was tested with 25 larvae and 25 pupae at each concentration (four replicates), and adult mortality was measured after 24 hours using WHO-modified tube tests. We performed probit analysis to find the LC₅₀ and LC₉₀ values. LC-MS profiling identified seven anthraquinones: physcion-8-O-β-D-glucoside, sennoside, aloin, chrysophanol-8-O-D-glucoside, aloe-emodin, emodin-8-O-β-D-glucoside, and notably, danthron, which was exclusively found in the fruit peel and pulp. The methanolic fruit peel extract had the highest larvicidal and pupicidal activity of all the extracts, with 24-hour LC₅₀ values of 92.80 mg/L and 102.12 mg/L, respectively. Moderate adulticidal efficacy (44.00% at 200 mg/L) was noted, with efficacy ranking as follows: fruit peel > fruit pulp > seed. The reduced effectiveness against adult mosquitoes may be due to their thicker, more sclerotized cuticle and elevated detoxification enzyme expression. These results indicate that C. fistula, especially its fruit peel, shows potential as a powerful, eco-friendly larvicide and pupicide, making it a sustainable plant-based option for use in programs to control dengue vectors.